TEKNIK SUPERVISI DAN EVALUASI PENDIDIKAN: KLASIFIKASI, IMPLEMENTASI, SERTA KELEBIHAN DAN KETERBATASANNYA - Euis Farida; Rinawati; Rahman Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of education cannot be separated from the effectiveness of planned and systematic supervision and evaluation. This article examines various techniques of educational supervision and evaluation, analyzes their implementation, and identifies the strengths and limitations of each technique. A library research method with a descriptive-analytical approach is employed. Findings indicate that supervision techniques fall into individual techniques (classroom visitation, classroom observation, individual conference, inter-class visitation, and self-evaluation) and group techniques (orientation meeting, teachers' meeting, study group, discussion, workshop, and experience sharing). Evaluation techniques include test techniques (written, oral, and performance) and non-test techniques (observation, interview, questionnaire, portfolio, rating scale, and reflective journal). An integrative approach combining various techniques synergistically represents the best strategy in supervisory and educational evaluation practice.